The effects of L1 on L2 writing and translation: A case study - Fujii, Yasunari (Journal of Modern Languages, 2017)
This article examines the perceptions and attitudes of Japanese university students regarding two types of writing tasks: writing directly in L2 and translating from L1 into L2. A total of 128 Japanese undergraduate students participated in the study and completed two activities – composition in English and translation of a passage from Japanese into English – followed by a questionnaire. An analysis of performance and results leads to the following conclusions: (1) while L2 writing was perceived to be more difficult, it received a higher preference rating, (2) when writing in L2, participants rely heavily on L1 during the drafting stage and translate their ideas from L1 into L2 in the composing stage, and (3) most participants draft in L1 and then translate into L2, restricting their choices to shorter sentences. The implications of the findings are applied to alternative teaching strategies to help learners succeed in their L2 writing endeavors.